SUFFERED, ALIENATED AND DEATH: REPRESENTATION OF HIV/AIDS IN FILM â€œMIKAâ€ (2013) - Faisal, Mochamad (Universitas Jember, 2024)
Films are often used as a medium to address ongoing issues in society, one of the examples is HIV/AIDS. A â€œdeath sentenceâ€ as results from â€œdeviant behaviorâ€ is still stigmatized and remains a major obstacle in mitigating the spread of the HIV up to the present day, since its first case in Indonesia back in 1987. One of Indonesian films that address the issue of HIV/AIDS is